Barro Colorado Island's phylogenetic assemblage structure across fine spatial scales and among clades of different ages. Issue 12 (1st December 2013) - Pearse, William D.; Jones, F. Andrew; Purvis, Andy
Abstract : Phylogenetic analyses of assemblage membership provide insight into how ecological communities are structured. However, despite the scale‐dependency of many ecological processes, little is known about how assemblage and source pool size definitions can be altered, either alone or together, to provide insight into how ecological diversity is maintained. Moreover, although studies have acknowledged that different clades within an assemblage may be structured by different forces, there has been no attempt to relate the age of a clade to its community phylogenetic structure. Using assemblage phylogenies and spatially explicit data for trees from Barro Colorado Island (BCI), we show that larger assemblages, and assemblages with larger source pools, are more phylogenetically clustered. We argue that this reflects competition, the influence of pathogens, and chance assembly at smaller spatial scales, all operating within the context of wider‐scale habitat filtering. A community phylogenetic measure that is based on a null model derived explicitly from trait evolution theory, D, is better able to detect these differences than commonly used measures such as SESMPD and SESMNTD . We also detect a moderate tendency for stronger phylogenetic clustering in younger clades, which suggests that coarse analyses of diverse assemblages may be missing important variation among clades. Our results emphasize the importance of spatial and phylogenetic scale in community phylogenetics and show how varying these scales can help to untangle complex assembly processes.